Employee’s Perspective of Organizational Service Quality Orientation - Othman, Hasbullah; Ibrahim, Irwan; Amer, Afizan; Kasdi, Saiful Azmir; Ismail, Albert Feisal@Muhd Feisal Bin (Innovations in Science and Technology Vol. 4, 2022)
Purpose: The purpose of this paper is to conduct an empirical research focusing on the elements of service quality on internal structural orientation from the employees’ perception. Design/Methodology/Approach: An empirical statistics were collected through a survey. The respondents of the survey are 102 workers including all staff in the organization. SPSS was used to validate the model with the data were collected within the organization. Findings – The findings showed that employee perceptions of service quality performance are influenced by organizational knowledge, service concept, service competence and job satisfaction instead of training and customer service orientation. Research Limitations/Implications: The authors performed the survey by distributed questionnaire personally to all staffs in the company. Given this, in order to test the stability of the findings in other contexts, a replication research is important to be performed in the future. Practical Implications: Internal organization quality service orientation practices should be implemented as an integrated system rather than independent practices, in which they interact with each other and improve employee service quality performance. Originality/Value: The empirical results of this study provide an evidence to consider the internal organization quality service orientation as reliable predictors for employee service quality performance. According to the research, these factors interact with each other and have effects on employee perceptions of service quality performance.